Validation of Hamdan intelligence scale in upper elementary grades using the Rasch model: exploratory study - Ayoub, Alaa Eldin A.; Aljughaiman, Abdullah M.; Alghawi, Mariam A.; Morsy, Ahmed; Omara, Ehab M. N.; Abdulla Alabbasi, Ahmed M.; Renzulli, Joseph S. (Frontiers in Psychology, 2024)
Hamdan Intelligence Scale (HIS) is the first intelligence scale that has been developed and normed in the United Arab Emirates (UAE). This study aimed to examine the refinement, validity, and reliability of HIS in upper elementary grades using the Rasch model. A total of 4,301 students (34.3% Male; 65.7% Female) from grade 4 to 6 (32.1% grade 4; 33.7% grade 5; 34.2% grade 6) were administered to the HIS. The confirmatory factor analysis was first conducted to verify the fitness of the one-factor model of the HIS. The results of validity showed strong correlation coefficients between the HIS and the Aurora-g battery (0.83) and the Raven’s Standard Progressive Matrices (RSPM; 0.86). Moreover, the results of the developmental trends demonstrated that raw scores of the HIS increase with age and grade relatively constantly across composite scores. Unidimensionality was confirmed through the Confirmatory Factor Analysis and Principal Component Analysis of Residuals (PCAR). The low eigenvalues of the first contrast were below 2, and additionally, the infit and outfit mean squares ranged from 0.88 to 1.14 and 0.84 to 1.14. Rasch’s person reliability result of 0.62 was acceptable reliability. The results provided strong support for the validity and reliability of using the Hamdan Intelligence Scale in the UAE environment.